Pt(ii) complex containing the 1R, 2R enantiomer of trans-1, 2-diamino-4-cyclohexene ligand effectively and selectively inhibits the viability of aggressive pancreatic adenocarcinoma cells and alters their lipid metabolism. Issue 13 (1st June 2022) - Novohradsky, Vojtech; Markova, Lenka; Kostrhunova, Hana; Svitelova, Marie; Kasparkova, Jana; Barbanente, Alessandra; Papadia, Paride; Margiotta, Nicola; Hoeschele, James D.; Brabec, Viktor
Abstract : New compounds structurally derived from oxaliplatin exhibit high potency in malignant pancreatic adenocarcinoma cells. Their mechanism of antiproliferative action in pancreatic cancer cells involves inhibition of de novo lipid synthesis. Abstract : Here, we investigated the mechanism of antiproliferative action in cancer cells of new compounds structurally derived from oxaliplatin, namely a pair of enantiomers [Pt(OXA)(1 R, 2 R -DACHEX)] (1 ) and [Pt(OXA)(1 S, 2 S -DACHEX)] (2 ) (OXA = oxalate, DACHEX = trans -1, 2-diamino-4-cyclohexene). While oxaliplatin is used almost exclusively to treat colorectal and other gastrointestinal cancers, new complex 1 shows instead high potency in malignant pancreatic adenocarcinoma PSN1 cells including superior selectivity for pancreatic cancer over noncancerous cells. Utilizing a multi-platform biochemical approach to study the unique features of the mechanism of action of this new platinum-based drug, we show that 1 has a much greater ability to penetrate pancreatic tumors than its S, S enantiomer 2 and oxaliplatin, and to be transported into cells as bound to plasma proteins. Additionally, the mechanism of action of 1 and, to a lesser extent, oxaliplatin in pancreatic cancer cells involves alterations of the lipogenesis pathway, namely inhibition of de novo lipid synthesis, acting by a new mechanism not yet considered for anticancer action of clinically used antitumor platinum drugs. These data highlight the functional diversity of platinum anticancer compounds and the potential benefits of finding new anticancer drugs applying a mechanism-based rationale.